PENGARUH PEMBELAJARAN KONTEKSTUAL MEDIA AUDIO DAN KEMAMPUAN BERPIKIR ILMIAH TERHADAP HASIL BELAJAR IPA SISWA KELAS IV SD - Oyok Sunaryo; Sholeh Hidayat; Dodi Sukmayadi (LP3M Universitas Muhammadiyah Muara Bungo, 2021)
The concept of science for most students is a difficult concept. Based on observations made during science learning in grade IV at SDN Pasirtenjo 3, it shows that teachers still use a teacher-centered learning approach. This condition is most likely one of the causes of low student learning outcomes in science subjects. This research was conducted with the aim of analyzing the effect of contextual learning with audio-visual media and scientific thinking skills on science learning outcomes for fourth grade elementary school students. The population in this study were all fourth grade students at SDN Pasirtenjo 3 in the academic year 2020/2021 totaling 60 people, the research sample was grade IV students at SDN Pasirtenjo 3 Pandeglang Regency totaling 30 people. The independent variables in this study were audio-visual media contextual learning and scientific thinking, while the dependent variable was science learning outcomes. The measurement of scientific thinking variables uses a questionnaire, while the learning outcomes use the science learning outcomes test in the form of multiple choice. The results showed that there were differences in science learning outcomes between students who studied contextual audio-visual media with contextual learning without audio-visual media. Then there is the influence of the interaction between contextual learning and scientific thinking skills on science learning outcomes. Furthermore, students' science learning outcomes with contextual learning using audio-visual media have higher scientific thinking abilities compared to contextual learning without audio-visual media. And there is no difference in the science learning outcomes of students with low scientific thinking skills with contextual learning using audio-visual media compared to contextual learning without audio-visual media.